Adult Granulosa Cell Tumor of the Testis: A Case Report with a Review of the Literature - Klaus-Peter Dieckmann; Julia Bertolini; Christian Wülfing (Case Reports in Urology)
Adult granulosa cell tumor (AGCT) of the testis represents a very rare testicular neoplasm that is poorly understood clinically. Here we report the case of a 22-year-old male who presented with unspecific scrotal symptoms. Scrotal sonography disclosed a 6 mm hypoechoic intratesticular lesion. Histological examination after orchiectomy revealed a homogeneous and well demarcated neoplasm with monomorphic cells with nuclear grooving and microfollicular formation of the so-called Call-Exner bodies. Immunohistology showed positive stainings of vimentin, calretinin, and inhibin with negative stainings of the typical germ cell tumor markers. Thus, the diagnosis of a benign AGCT was made. The patient is well one year after surgery. A total of 91 previous AGCT cases were identified in the literature. Median age of the cases reported to date is 44 years, median tumor size 3.2 cm. 54.3% of the AGCT cases were located on the left side. 12 cases (13.2%) were of malignant nature. Testis-sparing surgery would be the treatment of choice, but only two of all cases had received that procedure. The present report aims to increase the clinical knowledge of AGCT and specifically to increase the clinician’s vigilance with respect to testis-sparing surgery in probably benign testicular masses.